Analysis on the Difference of Impact Response between Single Coal-Rock Particle and the Box Structure-Based Tail Beam. (4th February 2021) - Wan, Li-rong; Li, Zhe; Yang, Yang; Li, Ran
Abstract : In the process of coal caving, the basis of identifying coal and rock by the vibration signal is the difference of the tail beam response when coal-rock impacts the tail beam, and the tail beam in the hydraulic support is a complex box structure with multiplate transverse and longitudinal welding, and the response difference of the box structure-based tail beam under the impact of coal-rock is not clear. Therefore, this paper studies the response difference of box structure-based tail beam when coal-rock particle impacts on the box structure-based tail beam. Firstly, through the construction and analysis of the impact theoretical model of the coal-rock particle and metal plate, it is found that the complex box structure of the tail beam makes it extremely difficult to establish the impact theoretical model of the coal-rock and box structure-based tail beam, so it is impossible to directly study the response of the box structure-based tail beam when the coal-rock impacts on the box structure-based tail beam by the theoretical method. Therefore, the impact simulation model of coal-rock particle and box structure-based tail beam is further established. Through the changes of kinetic energy and internal energy of the box structure-based tail beam system, the contact response of collision contact zone, and noncollision contact zone of the box structure-based tail beam, the response difference of box structure-based tail beam when coal-rock particle impacts on the box structure-based tail beam is analyzed. Then, by changing the impact speed and contact mode of the coal-rock particle, the effects of impact speed and the contact mode on the response difference of the box structure-based tail beam are studied separately. The conclusion shows that the response difference of the box structure-based tail beam under the impact of the coal particle and rock particle is obvious, and the difference increases as the impact speed increases, and the difference increases as the contact range increases.